A comparison of deep learning U‐Net architectures for semantic segmentation on panoramic X-ray images - Bin Mushfiq, Rahil; Zannah, Rafiatul; Bashar, Mubtasim; Alam, Md. Nafidul; Rahman, MD Aftabur (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.